Contribuições para comunicação e computação quânticas: análise do PMD e PDL em um sistema de DQC, geração de um estado entrelaçado de quatro modos e uma porta CNOT para qubits de estados coerentes - Oliveira, Maria do Socorro Ribeiro de (2013)
This work presents contributions to the quantum communication and in computation fields. In the area of quantum communication, we analyzed the impacts of the effects of PMD and PDL on the performance of a quantum key distribution system based on BB84 protocol in a fiber optic network. It was presented an analytical expression for the average fidelity as a function of the PMD and PDL parameters which makes possible to analyze the behavior of bit error and secure bit generation rates for a quantum communication system. In the field of quantum computing, we proposed two optical systems based on linear optics for coherent state qubits. The first system is a probabilistic generator of a four-mode-type entangled state with a maximum efficiency of 25%. From this it state was possible to propose a second system that is able to perform a probabilistically CNOT gate. Both proposed systems may be implemented with existing photonics technology. They do not use single-qubit gate or quantum teleportation that are commonly used in quantum information processing using coherent states.